Analisis Model Pembelajaran Berdasarkan Teori Belajar: Implikasi Filosofis dan Aplikatif dalam Pendidikan Agama Islam - Hanifah Sabrina Aulia; Muhammad Fariq Faza; M. Yunus Abu Bakar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of the Industrial Revolution 4.0 to the Society 5.0 era presents new challenges for education, including Islamic Religious Education (PAI). PAI is required not only to transfer religious knowledge but also to shape character, morality, and 21st-century competencies. This study aims to examine the philosophical foundations, characteristics, and application of PAI learning models to ensure their relevance in modern education. The research employed a qualitative approach with a library research design, involving the exploration of primary and secondary literature, critical reading, systematic note-taking, and content analysis validated through triangulation of classical and contemporary sources. The findings indicate that PAI learning models are conceptual, theoretical, systematic, and rooted in religious, philosophical, psychological, and sociological foundations. Four main models behavioristic, information processing, social, and humanistic each have strengths and limitations, yet their integration is relevant to forming insan kamil, a holistic human being balanced in cognitive, affective, psychomotor, spiritual, and social aspects. Therefore, developing PAI learning models based on Islamic philosophy and adaptive to technological advancements is a strategic necessity to face global challenges.